TSC1 deficiency drives immune evasion in colorectal cancer via mTORC1-mediated dysregulation of PD-L1 sialylation - Guan, Xuemei; Zhang, Fengru; Tang, Yao; Bai, Pengyu; Wang, Wenyuan (Frontiers in Immunology, 2025)
BackgroundTSC1 serves as a critical regulator of the mTORC1 signaling pathway with established roles in colorectal cancer pathogenesis. This investigation systematically examined the clinical relevance of TSC1 in colorectal cancer and its mechanistic relationship with sialylation-mediated immune regulation through integrated analysis of TCGA datasets and experimental validation.MethodsWe employed bioinformatic analysis of TCGA cohorts combined with in vitro and in vivo experimental models. Molecular mechanisms were interrogated using biochemical assays, transcriptional profiling, and targeted pathway interventions. Sialylation dynamics were quantified through lectin-binding assays and surface plasmon resonance analysis.ResultsClinical analysis revealed that reduced TSC1 expression was significantly associated with poor prognosis in patients with colorectal cancer. Loss of TSC1 markedly activated the mTORC1 signaling pathway and induced upregulation of the sialyltransferase ST6GALNAC1 together with downregulation of the sialidase NEU4, thereby enhancing α2,6-sialylation on the cell surface. Treatment with rapamycin suppressed these alterations, whereas TSC1 knockdown partially reversed the inhibitory effects of rapamycin. This metabolic reprogramming led to increased α2,6-sialylation of PD-L1, which in turn elevated its protein stability and binding affinity to PD-1, ultimately resulting in T cell dysfunction and promoting tumor immune evasion. Both cellular and animal models demonstrated that pharmacological inhibition of mTORC1 or downregulation of ST6GALNAC1 effectively alleviated the aberrant PD-L1 glycosylation caused by TSC1 deficiency, thereby restoring the function of tumor-infiltrating CD8+ T cells and suppressing tumor progression.ConclusionOur findings demonstrate that TSC1 deficiency promotes immune evasion through mTORC1-mediated reprogramming of PD-L1 glycosylation, particularly α2,6-sialylation. This study identifies TSC1 as a prognostic biomarker and defines the TSC1/mTORC1/glycosylation axis as a potential therapeutic target to improve immune suppression in colorectal cancer, providing fundamental insights for the development of precision immunotherapy strategies.